Artistic Research: A Vibrant and Ever-Changing Field - Tomlinson, Vanessa (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This article looks at artistic research from an Australian perspective, with an emphasis on the role professional doctorates have played in developing this field. In 2017, I co-wrote "Two Decades of Artistic Research: The Antipodal Experience," which examined the state of artistic research in Australia at that time. Six years later, revisiting this body of work, I am reminded of how important the training of doctoral candidates is to the expansion and maturation of artistic research. In this writing, I share some best practice theses from the discipline of music, and share some of the tensions and successes in how universities measure creative research output.